2013
DOI: 10.1007/s12350-012-9663-1
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomography in the assessment of left ventricular function in healthy rats: A comparison of four imaging methods

Abstract: Relative to reference standard MRI measurements of LVEF, there was excellent agreement between PET-based measurements, notably for the novel blood-pool tracer (68)Ga-albumin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…The raw conduction (volume) signal is recorded in volts, therefor the predicted EDV is used to convert the peak voltage for each cardiac cycle to the maximum volume and the predicted SV is used to scale the amplitude of the voltage signal. fits (using (1) to literature data from catheter [33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52] and MRI-based measurement modalities [34,35,37,39,40,41,42,44,47,48,49,50,51]. Error bars denote the standard deviation from each study.…”
Section: Volume-conductance Calibrationmentioning
confidence: 99%
“…The raw conduction (volume) signal is recorded in volts, therefor the predicted EDV is used to convert the peak voltage for each cardiac cycle to the maximum volume and the predicted SV is used to scale the amplitude of the voltage signal. fits (using (1) to literature data from catheter [33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52] and MRI-based measurement modalities [34,35,37,39,40,41,42,44,47,48,49,50,51]. Error bars denote the standard deviation from each study.…”
Section: Volume-conductance Calibrationmentioning
confidence: 99%
“…Finally, many different methods for labeling serum albumins and other compounds with fluorine-18 for PET blood pool imaging have been reported [610]. While any of these methods might offer some advantages in certain circumstances, these methods do not appear to meet simultaneously the criteria for pre-clinical and clinical blood pool imaging we have set forth.…”
Section: Discussionmentioning
confidence: 99%
“…However, while a variety of PET blood pool labels have been developed [610], no PET blood volume imaging agent is today in general widespread use for routine measurement and visualization of regional blood volume in either clinical or animal studies. Accordingly, the goal of the present work was to identify and synthesize a blood pool-imaging agent with potential for commercialization and wide-spread use in both clinical and animal PET imaging applications.…”
Section: Introductionmentioning
confidence: 99%
“…The feasibility of cardiac output and stroke volume (SV) estimations at first-pass by means of the Stewart-Hamilton indicator-dilution principle has already been demonstrated using either 82 Rb [ 18 ], 18 FDG [ 19 ], or 15 O-water PET [ 20 ], the provided estimates being in close agreement with those of RBC-SPECT, echocardiography, and CMR. Todica et al described LV volume and function measurements in healthy rats using first-pass gated 18 FDG PET [ 21 ], without significant difference compared to CMR in terms of ejection fraction. Such cardiac function assessment using first-pass gated PET has been poorly investigated in humans since only two studies are reported on the feasibility of LV function assessment using first-pass gated 15 O-water PET [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%